Conceptual Design of Semi-Automatic Wheelbarrow to Overcome Ergonomics Problems Among Palm Oil Plantation Workers - N. S. M., Nawi; B. M., Deros; M. N., A. Rahman; Ezrin Hani, Sukadarin; N., Nordin; S. B. M., Tamrin; S. A., Bakar; M. L., Norzan (IOP Publishing, 2015)

(untitled)
An ergonomics problem is one of the main issues faced by palm oil plantation workers especially during harvesting and collecting of fresh fruit bunches (FFB). Intensive manual handling and labor activities involved have been associated with high prevalence of musculoskeletal disorders (MSDs) among palm oil plantation workers. New and safe technology on machines and equipment in palm oil plantation are very important in order to help workers reduce risks and injuries while working. The aim of this research is to improve the design of a wheelbarrow, which is suitable for workers and a small size oil palm plantation. The wheelbarrow design was drawn using CATIA ergonomic features. The characteristic of ergonomics assessment is performed by comparing the existing design of wheelbarrow. Conceptual design was developed based on the problems that have been reported by workers. From the analysis of the problem, finally have resulting concept design the ergonomic quality of semi-automatic wheelbarrow with safe and suitable used for palm oil plantation workers.